2020
DOI: 10.1016/j.ejca.2019.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptive and intrauterine device use and the risk of cervical intraepithelial neoplasia grade III or worse: a population-based study

Abstract: Objective: Hormonal contraceptive use has been associated with the development of cervical cancer, although inconsistent results are reported on the association with intrauterine device (IUD) use. The aim of this study was to evaluate the association between the type of contraceptive use and the development of cervical intraepithelial neoplasia grade III or worse Abbreviations: ASC-H, atypical squamous cells e cannot rule out high-grade squamous intraepithelial lesion; ASC-US, atypical squamous cells of undete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Also, we did not have data on several other possible confounders such as sexual behaviour and oral contraceptive use. 43 It has been shown that a higher proportion of women with inflammatory bowel disease have sexual dysfunction compared with matched controls. 44 Since sexual activity is a strong risk factor for CIN, 32 it might be hypothesised that the association with IBD is even stronger.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we did not have data on several other possible confounders such as sexual behaviour and oral contraceptive use. 43 It has been shown that a higher proportion of women with inflammatory bowel disease have sexual dysfunction compared with matched controls. 44 Since sexual activity is a strong risk factor for CIN, 32 it might be hypothesised that the association with IBD is even stronger.…”
Section: Discussionmentioning
confidence: 99%
“…OC users had an increased risk of CIN3+ compared with IUD users; RR 1.83 (95% CI 1.60–2.09). Results for cervical cancer pointed in the same direction but were statistically significantly increased in OC users only ( Loopik et al , 2020 ).…”
Section: Discussionmentioning
confidence: 67%
“…A comparison was made between our results and two previous studies investigating the risk of precancerous cervical lesions associated with use of HIUD, CIUD, and OC ( Averbach et al , 2018 ; Loopik et al , 2020 ).…”
Section: Methodsmentioning
confidence: 79%
“…Our analysis results showed that women aged 20-35 and those who had used oral contraceptives for more than 1 year were more likely to develop CIN1+. Oral contraceptive use has been reported to increase the risk of developing cervical cancer in women with normal cytology in a retrospective population-based cohort study [30]. Recently, a UK prospective cohort study found that the progression probability of normal cervical cytology to CIN2+ decreased with age, with the highest in the 25-34 years old population [31].…”
Section: Discussionmentioning
confidence: 99%